Research on Classification Evaluation and Strategy of Utilization of Historical Buildings - Taking 54 Historical Buildings in Beijing Old City as an Example - Yuefang, Rong; Jian , Song; Dian, Zhang (MAJ - Malaysia Architectural Journal, 2025)
Historic buildings are important manifestations of historical, artistic, and scientific values from different periods, and they are important research objects for urban historical and cultural studies. Strengthening the rational utilization of historic buildings is an inevitable trend in current development. There have been practical explorations in the open use of historic buildings in various places, some experiences have been accumulated in terms of engineering techniques, social participation, and management operations. However, at this stage, the open use of historic buildings is mostly in the pilot exploratory stage, and there is still a lack of overall planning. The construction of a scientific and effective evaluation index system for the openness and appropriateness of the use of historic buildings is the first prerequisite for the protection and rational use of historic buildings, and it is also a powerful support for the complete demonstration of the city’s historical features. Based on this, this article focuses on the characteristics of historic buildings, and constructs an indicator system for evaluating the potential of open use of historic buildings from three dimensions: current conditions, value endowment, and external environment of historic buildings. Combining different forms of open use of historic buildings, it studies and determines the evaluation criteria for each indicator from six aspects: visiting and touring, cultural display, business services, public office, community services, and state services. Taking 54 historical buildings in Beijing old city as an example, the article applies a classification evaluation method to provide reference for the overall planning and categorized management of the open use of historical buildings in Beijing old city.